Sosialisasi Strategi Pembangunan Wisata Halal di Kecamatan Pakis, Kabupaten Malang, Jawa Timur: Socialization of Halal-Tourism Development Strategies in Pakis, Malang, East Java - Noor, Iswan; Muttaqin, Aminnullah Achmad; Ikaputri, Adelia Dianti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The tourism sector is one of the supporting sectors of the Indonesian economy. With the most significant number of Muslim communities in the world, Indonesia has the ambition to become the leading halal tourist destination for tourists from all countries. In achieving its goals, a team called the Team for the Acceleration of Halal Tourism Development was formed under the Ministry of Tourism of the Republic of Indonesia. This team made a list of 10 prioritized halal tourist destinations in Indonesia, one of which is East Java, especially the Malang Raya area. In addition to cultural, shopping, and culinary tourism, Malang Raya offers high-quality natural tourism spots, supported by the freshness of the air and water. An area in Malang, called Pakis, has a spring that has excellent exploration potential to be utilized for halal and family-friendly water tourism. Therefore, socialization needs to be done to prepare the locals to build halal tourism, which is expected to bring goodness to their lives.